First Nationwide Molecular Screening Program in Spain for Patients With Advanced Breast Cancer: Results From the AGATA SOLTI-1301 Study - Pernas, Sonia; Villagrasa, Patricia; Vivancos, Ana; Scaltriti, Maurizio; Rodón, Jordi; Burgués, Octavio; Nuciforo, Paolo; Canes, Jordi; Paré, Laia; Dueñas, Marta; Vidal, Maria; Cejalvo, Juan Miguel; et al. (Frontiers in Oncology, 2021)
Background The SOLTI-1301 AGATA study aimed to assess the feasibility of a multi-institutional molecular screening program to better characterize the genomic landscape of advanced breast cancer (ABC) and to facilitate patient access to matched-targeted therapies in Spain. Methods DNA sequencing of 74 cancer-related genes was performed using FFPE tumor samples in three different laboratories with three different gene panels. A multidisciplinary advisory board prospectively recommended potential targeted treatments. The primary objective was to determine the success of matching somatic DNA alteration to an experimental drug/drug class. Results Between September 2014 and July 2017, 305 patients with ABC from 10 institutions were enrolled. Tumor sequencing was successful in 260 (85.3%) patients. Median age was 54 (29-80); most tumors were hormone receptor-positive/HER2-negative (74%), followed by triple-negative (14.5%) and HER2-positive (11.5%). Ninety-seven (37%) tumor samples analyzed proceeded from metastatic sites. Somatic mutations were identified in 163 (62.7%) patients, mostly in PIK3CA (34%), TP53 (22%), AKT1 (5%), ESR1 (3%), and ERBB2 (3%) genes. Significant enrichment of AKT1 mutation was observed in metastatic versus primary samples (9% vs. 2%; p=0.01). Genome-driven cancer therapy was recommended in 45% (n=116) of successfully screened patients, 11% (n=13) of whom finally received it. Among these patients, 46.2% had a PFS of ≥6 months on matched therapy. Conclusions AGATA is the first nationwide molecular screening program carried out in Spain and we proved that implementing molecular data in the management of ABC is feasible. Although these results are promising, only 11% of the patients with genome-driven cancer therapy received it.